Conductivity Insights Into the Carbon Nanotubes Mobility Restricted by the Long‐Branched Chains During the Thermal Annealing, Fast Shear Flow and Melt to Solid Cooling Process - Jixiang Li; Abderrahim Maazouz; Khalid Lamnawar (Macromolecular Materials and Engineering)
Abstract The present work provides a unique insight to reveal the long chain branching (LCB) influence to the nano‐fillers, that is via analyzing the conductivity evolution during the thermal annealing, fast shear flow and melt to solid cooling process. Meanwhile the crystallization behavior is also discussed. A linear polypropylene (PPC) and a long chain branched polypropylene (PPH) are chosen as the two polymer matrices with carbon nanotubes (CNTs) as the nanofillers. During the thermal annealing process, a more obvious growth of electrical conductivity of linear PPC nanocomposites are observed compared with LCB PPH nanocomposites. The harder movement of CNTs inside LCB PPH matrix may be the main reason. This also can be reflected by the conductivity evolution during slow cooling process where a decrease‐then‐increase (DTI) phenomenon is found for PPC/CNTs systems due to the rebuilding of CNTs conductivity network after crystallization. By contrast, this does not happen for PPH/CNTs systems.